2021
DOI: 10.5483/bmbrep.2021.54.12.107
|View full text |Cite
|
Sign up to set email alerts
|

Precise control of mitophagy through ubiquitin proteasome system and deubiquitin proteases and their dysfunction in Parkinson's disease

Abstract: Parkinson's disease (PD) is one of the most common neurodegenerative diseases in the elderly population and is caused by the loss of dopaminergic neurons. PD has been predominantly attributed to mitochondrial dysfunction. The structural alteration of α-synuclein triggers toxic oligomer formation in the neurons, which greatly contributes to PD. In this article, we discuss the role of several familial PD-related proteins, such as α-synuclein, DJ-1, LRRK2, PINK1, and parkin in mitophagy, which entails a selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…These results demonstrated that NL-1 or mitoNEET shRNA may attenuate CCCP-induced mitochondrial ROS production through the upregulation of the expression of antioxidant defense genes with enhanced mitophagy. Furthermore, PGC-1α, as a major regulator of mitochondrial biogenesis, maintains a network of healthy mitochondria by balancing the generation of new organelles and the removal of damaged mitochondria ( 8 , 22 ). We did another experiment to demonstrate that mitoNEET inhibition induces the activation of mitochondrial biogenesis via the increase of PGC-1α and the activation of mitophagy via increase of Drp-1 (a fission protein) and decrease of mitofusin 2 (Mfn2; a fusion protein) in the presence with CCCP by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results demonstrated that NL-1 or mitoNEET shRNA may attenuate CCCP-induced mitochondrial ROS production through the upregulation of the expression of antioxidant defense genes with enhanced mitophagy. Furthermore, PGC-1α, as a major regulator of mitochondrial biogenesis, maintains a network of healthy mitochondria by balancing the generation of new organelles and the removal of damaged mitochondria ( 8 , 22 ). We did another experiment to demonstrate that mitoNEET inhibition induces the activation of mitochondrial biogenesis via the increase of PGC-1α and the activation of mitophagy via increase of Drp-1 (a fission protein) and decrease of mitofusin 2 (Mfn2; a fusion protein) in the presence with CCCP by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…4 ). Particularly, as PGC-1α is a major regulator of mitochondrial biogenesis, the balance of elevated PGC-1α and mitophagy assures maintenance of the mitochondrial contents ( 8 , 22 ). CCCP-induced ROS, disequilibrium of mitochondrial homeostasis cause deterioration of mitochondrial function and cell death ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These targets comprise, for example, a group of import receptors and ion channels such as TOM20, VDAC1 or VDAC3, and Mfn1 and Mfn2 proteins involved in the process of fusion and fission to block the fusion of defective mitochondria and Miro proteins ( Geisler et al, 2010 ; Wang X. et al, 2011 ; Sun et al, 2012 ; Bingol et al, 2014 ; Birsa et al, 2014 ; Choubey et al, 2014 ). Parkin further facilitates K48 and K63 ubiquitination of substrates and recruits the autophagy machinery and complexes of lysosomal degradation ( Olzmann et al, 2007 ; Moore et al, 2008 ; Richard et al, 2020 ; Park et al, 2021 ). Degradation of Miro by Parkin is a prerequisite for the arrest of mitochondrial movement, so that clearance of mitochondria can properly proceed ( Wang X. et al, 2011 ; Birsa et al, 2014 ).…”
Section: Miro Proteins Their Structure and Functionmentioning
confidence: 99%